(3Gdefi aj Gdcfis - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hGdUdGI Ydi QShd Gddg gPg cQGSI LQOJ ajgG cfi CYdGe GdCLfGS ef GdeQUY dGHf GdCKjQ eQJH Ydi MQha GdeYLe hSejJg HGdefi aj Gdcfis
(3BNQgG (B:s
(3ajbGd dg gPG CHh adGf hgPG CHh adGf jYfhf CHG GdUHjGf GdPj YfOge hcGf jYQage HEPGaJge Edi CHfGFge aef XgQJ Gdcfi aj GdYQH Ke GTJgQJ hGJSYJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B2 / 1888s
(3TPQGJ GdPgH (B8 /51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs